Yet another question 4 - Corrected

Algebra Level 5

Let a k = ( k 2 + 1 ) k ! a_k = (k^2 +1) k! and b n = k = 1 n a k b_n = \displaystyle \sum_{k=1}^{n} a_k .

a 100 b 100 \dfrac{a_{100}}{b_{100}} can be represented as A B \dfrac AB for positive coprime integers A A and B B .

Find B A B-A .


Details and assumptions


Try more here


The answer is 99.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Aditya Sky
Apr 29, 2016

Note that a k a_k can be written as :- a k = ( k 2 + 1 ) k ! = ( ( k + 1 ) 2 2 k ) k ! = ( k + 1 ) ( k + 1 ) ! 2 k k ! = ( ( k + 1 ) ( k + 1 ) ! k k ! ) k k ! a_k=\,(k^{2}+1)\cdot k!\,=\,\left((k+1)^{2}-2k\right)\cdot k!\,=\,(k+1) \cdot (k+1)! - 2k \cdot k!\,=\,\left((k+1)\cdot (k+1)!-k \cdot k!\right)-k\cdot k! . Now, b n = k = 1 n a k = k = 1 n ( ( k + 1 ) ( k + 1 ) ! k k ! ) k k ! = k = 1 n ( k + 1 ) ( k + 1 ) ! k k ! k = 1 n k k ! = k = 1 n ( k + 1 ) ( k + 1 ) ! k k ! Telescopic Series k = 1 n ( k + 1 ) ! k ! Telescopic Series = ( ( n + 1 ) ( n + 1 ) ! 1 ) ( ( n + 1 ) ! 1 ) ) = n ( n + 1 ) ! b_n\,=\,\sum_{k=1}^{n}a_k\,=\, \sum_{k=1}^{n} \left( (k+1) \cdot (k+1)! - k \cdot k!\right) - k \cdot k! \,\\ =\,\sum_{k=1}^{n} (k+1) \cdot (k+1)! - k\cdot k!\,-\,\sum_{k=1}^{n} k\cdot k!\,\\ =\, \underbrace{\sum_{k=1}^{n} (k+1) \cdot (k+1)! - k\cdot k! }_{\text{Telescopic Series}}\,-\,\underbrace{\sum_{k=1}^{n} (k+1)! - k!}_{\text{Telescopic Series}}\,\\ =\, \left((n+1) \cdot (n+1)!-1)- \left((n+1)! - 1\right)\right)\,\\ =\,n \cdot (n+1)! . Hence, b n = n ( n + 1 ) ! b_n\,=\,n \cdot (n+1)! .

Now, a 100 b 100 = ( 10 0 2 + 1 ) 100 ! 100 101 ! = 10 0 2 + 1 100 101 \large\frac{a_{100}}{b_{100}}\,=\,\frac{(100^{2}+1) \cdot 100!}{100 \cdot 101!}\,=\,\frac{100^{2}+1}{100 \cdot 101} .

Hence, b a = 100 101 ( 10 0 2 + 1 ) = 100 101 10 0 2 1 = 100 ( 101 100 ) 1 = 100 1 = 99 b-a\,=\,100 \cdot 101 - ( 100^{2} + 1 )\,=\,100 \cdot 101 - 100^{2} - 1\,=\, 100(101 - 100) -1 \,=\, 100 -1\,=\, \boxed{99} .

Moderator note:

Great clear explanation! Keep it up :)

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...